Analysis and Mitigation of High-Pressure and High-Temperature Well Completion Design of Elkin/Franklin Fields in the North Sea - Shaheed, Luay Hameed (Journal of Petroleum Research and Studies, 2022)
The development of High-Pressure and High-Temperature (HP/HT) wells is accompanied by high risk, and still represents one of the greatest technological challenges for the oil and gas industry related to the equipments used and their ability to sustain these conditions. The results analysis of data is key to investigating reasons for bad performances and failures of well completion design and detecting at an early stage potential downhole events. This paper applies machine learning to the results of real data analysis of deep and deviated well in the HP/HT environment. It presents techniques used to analyze design limits for the tubing string of the well with different rates of production and water injection, and predict pressure and temperature when multiple operations are applied to the tubular string during the well’s lifetime. It also analyzes the most important parameters that impact the tubular string, such as temperature effect, safety factors, and tubing length change. A simulation model for a well has been developed to accomplish the objective of this work by using WellcatTM software modules (Prod & Tube) based on real data from the Elgin/Franklin fields in the North Sea. Two designs of tubular string were used to analyze design limits; the first included a tubing size of 4 ½ in and a latched permanent packer, and the second was identical to the first one but included an expansion joint tool to allow free movement of the tubing, and it was used to mitigate the first well completion design failure. Based on the results of this paper, three load cases (produce-6 months, tubing leak, and water injection) failed in the first design when the rates of oil production and water injection were increased to 12000 bbl/d and 5000 bbl/d respectively, whilst all load cases fell into the triaxial envelope and met the axial criteria in the second design. Furthermore, the predicted results of pressure and temperature for the tubing and surroundings indicate the tubular string could be exposed to buckling problems and serious thermal expansion in the annulus. As well, tubing length can be changed (elongated or shortage) owing to thermal effects during multiple load cases.